CORRELATION OF MALNUTRITION, WORM INFECTION, PARENTS, INCOME AND KNOWLEDGE ON ANEMIA PREVALENCE AMONG 6-9 YEAR OLD STUDENTS OF LILIBA INPRES ELEMENTARY SCHOOL - Marni Tangkelangi (Universitas Nahdlatul Ulama Surabaya, 2019)
Anemia in school–age children will not only cause harm to health but also will have impact on students learning achievement. Thus, anemic children will indirectly affect the national development. The aim of this study is to observe the correlation between malnutrition, worm infection, parents income and knowledge on anemia prevalence among 6–9 years old children. The method of this research was a cross sectional study with a simple random sampling technique, consisted of 222 participants from Liliba Inpres Elementary School. This study was done by measuring children Body Mass Indeks (BMI) ––age to measure the z score and compare to WHO Children growth standard, by using microscope examination with direct method for identifying helminthiasis, by using questionaries to measure the parent knowledge and parent income and also by measuring haemoglobin values using POCT Device. The results showed that there are correlations between malnutrition and worm infection on anemia prevalence (p value 0.000). However, there are no correlations between parent’s knowledge (p value 0.469) and parent’s income on anemia prevalence among 6–9 years old children on Liliba Inpres Elementary School (p value 0.606). In conclusion, these findings confirm that malnutrition and worm infection was correlated with anemia prevalence on Liliba Inpres Elementary School Students so that they are advised to manage their nutritional intake and to practice personal hygiene.